The Effect of Warm Red Ginger Compress Therapy on the Decrease in Rheumatoid Arthritis Pain in the Elderly at the Social Institution Tresna Werdha Pagar Dewa Bengkulu - Andri Kusuma Wijaya1 , Ferasinta1 , Yandrizal2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: This study aims to determine the effect of compress therapy using warm red ginger to reducethe scale of rheumatoid arthritis pain in the elderly.Study Design:This study used a one-group pretest-posttest pre-experimental research design, with a totalsample of 15 respondents.Results:Based on the results of the bivariate analysis using the Dependent T test, it was found that therewas an effect between compresses using warm red ginger with a value (p value = 0, 000) on the decrease inthe scale of rheumatoid arthritis pain in the elderly at the Tresna Werdha Pagar Dewa Bengkulu Home. Theprovision of non-pharmacological management in the form of compressing warm red ginger will providea heat effect so that it can eliminate inflammation and acidity in the fluid content in the joints, besides thatthere is also gingerol content in the area around the ginger rhizome which has an analgesic effect withtechniques to create vasodilation conditions in vessels. blood resulting in decreased pain. Therefore, givingthis therapy is very beneficial and helps the elderly who suffer from rheumatoid arthritis pain.ConclusionThe role of the orphanage will be very helpful in informing and facilitating the elderly in reducingthe scale of rheumatoid arthritis pain through non-pharmacological management in the form of warm redginger compress therapy with the hope of improving the health status of the elderly at the social institutionTresna Werdha Pagar Dewa Bengkulu Home.